2017
DOI: 10.1177/2333393617740463
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Students’ Attitudes About Alcohol Consumption During Pregnancy: Responses to Narrative Vignettes

Abstract: This article explores medical, midwifery, and nurse practitioner students’ attitudes about women who may consume alcohol throughout their pregnancies. Twenty-one health care students responded to a scenario-based vignette addressing alcohol consumption during pregnancy, as well as a semistructured interview, which were analyzed using Braun and Clarke’s thematic analysis approach. Two primary themes related to students’ attitudes concerning alcohol consumption during pregnancy were identified: (a) divergent rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…It has also been hypothesized that the amount of stress university students are put under could enhance alcohol consumption in this population [84]. It has been reported that healthcare student's positions and beliefs about alcohol are still unclear and probably stereotyped [85]. Furthermore, specific clinical placements in alcohol rehab facilities were proved effective in sensitizing students about alcohol abuse disorder [86].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been hypothesized that the amount of stress university students are put under could enhance alcohol consumption in this population [84]. It has been reported that healthcare student's positions and beliefs about alcohol are still unclear and probably stereotyped [85]. Furthermore, specific clinical placements in alcohol rehab facilities were proved effective in sensitizing students about alcohol abuse disorder [86].…”
Section: Discussionmentioning
confidence: 99%
“…Coons et al [27] suggest that providing advice on alcohol use and pregnancy is neither routine or consistent in health care practice, and that embedding clear, balanced and consistent messaging within clinical practice is a critical aspect of prevention. However, as they elsewhere note [28], providing such advice is further challenged by varying levels of knowledge, education and training on FASD, as well as personal beliefs regarding women’s autonomy and pre-existing beliefs and subjective biases regarding who uses alcohol during pregnancy. It is recognized that the topic of alcohol use and pregnancy can be uncomfortable for health care providers to address, and confusion exists about whose role it is in the health care system to respond to this concern.…”
Section: Introductionmentioning
confidence: 99%
“…We also found a high agreement with the idea that an FASD policy should include programmes for screening for alcohol use at clinics and hospitals and proper documentation of the history of alcohol use. Therefore, healthcare providers must be equipped with the necessary skills to have informed discussions on alcohol use with women [44, 46]. Discussing alcohol consumption and documenting its history also forms part of the recommendations of the Canadian framework for action on FASD, and the Australian action plans for FASD [34, 36, 37].…”
Section: Discussionmentioning
confidence: 99%